KEPUTUSAN WISATAWAN PRANCIS BERLIBUR KE BALI PADA ERA NEW NORMAL - Endi, Ferhadius; Prasetyo, Danang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
This study discusses the decision of French tourists on their planned visit to Bali in the new normal era in 2021. This research is a qualitative descriptive study. Data was obtained by means of online interviews and questions and answers via email to 35 potential tourists. Based on the results of research that has been done, it was found that two decisions of French tourists regarding their vacation plans to Bali, namely: (1) Cancellation of tour trips with the consideration of (a) changes in tourist budgets and financial plans, (b) health reasons for tourists, (c) difficulty in managing time, and (d) the uncertainty of the global situation. (2) Delay or reschedule Tour trips. The factors that influence tourists to continue their travel agenda to Bali with a note of rescheduling, namely: (a) Advances that have been paid to travel agents, (b) the need for post-lockdown holidays during 2020, and ( c) vaccination as an effort to protect the tourists from Covid-19. The hope is that the exposure of the research results can be a reference for researchers, tourism service business actors, and tourists to work together to implement health protocols in all tourism activities for a better Indonesian tourism. Keywords: French Tourists, Bali Tourism, New Normal